The little goat - Dunn, Judy.; Dunn, Phoebe (New York : Random House, 1978)
Andy receives a little goat as a birthday present. He names him Sam and they soon become best friends.
2.0
K-3
K-3
Keywords: Goats -- Fiction; Pets -- Fiction; Goats -- Fiction; Pets -- Fiction